2017
DOI: 10.1017/s0033291717000848
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive beliefs mediate the effect of emotional abuse on depressive and psychotic symptoms in severe mental disorders

Abstract: Our results indicate that early emotional abuse is relevant to depression/anxiety and positive symptoms in bipolar and psychotic disorders, and suggest that metacognitive beliefs could play a role in an affective pathway to psychosis. Metacognitive beliefs could be relevant treatment targets with regards to depression/anxiety and positive symptoms in bipolar and psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 71 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…Current findings, together with the fact that ranges of MCQ measures when given were broad, suggest that dysfunctional metacognitions could develop at an early age. This is consistent with findings that suggest there may be childhood factors that lead to vulnerability to the development of these metacognitions, such as early experiences of emotional abuse (e.g., Myers and Wells, 2015; Østefjells et al, 2017) and parenting style (Gallagher and Cartwright-Hatton, 2008; Spada et al, 2012; Lønfeldt et al, 2017b).…”
Section: Discussionsupporting
confidence: 86%
“…Current findings, together with the fact that ranges of MCQ measures when given were broad, suggest that dysfunctional metacognitions could develop at an early age. This is consistent with findings that suggest there may be childhood factors that lead to vulnerability to the development of these metacognitions, such as early experiences of emotional abuse (e.g., Myers and Wells, 2015; Østefjells et al, 2017) and parenting style (Gallagher and Cartwright-Hatton, 2008; Spada et al, 2012; Lønfeldt et al, 2017b).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the risk of PTSD (and other internalizing psychiatric disorders) may not only be predicted by the quantity and quality of traumatic exposure(s), but also by when in the developmental period these events occurred. The experience of trauma in childhood, in particular, can influence the development of negative schemas about the self, others, and the world (Beck, 2008;Jacobs, Reinecke, Gollan, & Kane, 2008), which ultimately increase vulnerability to disorders such as depression, anxiety, and PTSD (Ostefjells et al, 2017). Explaining sex differences in risk of developing certain psychiatric disorders are, however, a complex and sensitive issue, and almost certainly encompass many interacting evolutionary, biological, psychological, social, and methodological factors (Olff, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups have also reported that social support may be protective and interventions targeting enhancing social support may decrease disease vulnerability and improve illness course [179]. Metacognitive beliefs, or beliefs about one's own cognition, are suggested to mediate the relationship between childhood maltreatment and mood-related and positive symptoms in individuals with psychotic or bipolar disorder [180]. Specifically, beliefs about thoughts being uncontrollable/dangerous mediated the relationship between emotional abuse and depression/anxiety and positive symptoms subscale scores on the Positive and Negative Syndrome Scale (PANSS).…”
Section: Pathways To Mood Disorder Outcomes-more Work On Mechanisms Amentioning
confidence: 99%